The Role of Zakat in the Islamic Economy: A Case Study on Zakat Literacy in Parepare, Indonesia - Alifkah, Ayu; Hannani, Hannani; Damirah, Damirah; Semaun, Syahriyah; Bahri, Andi (Universitas Muhammadiyah Makassar, 2025)
Zakat is not only an act of worship to Allah but also a vital instrument for enhancing social welfare when managed effectively. In Ajatappareng, the potential for zakat is substantial; however, actual collections have yet to meet targeted levels. This shortfall is largely attributed to limited understanding and awareness among potential payers. This study aims to examine the collaborative governance process in zakat management by BAZNAS Ajatappareng. The research adopts the collaborative process framework of Ansell and Gash, which includes four dimensions: initial conditions, leadership, institutional design, and collaborative process. A qualitative phenomenological approach was employed, with data collected through observation, interviews, and supporting documents. Informants were selected via purposive sampling, and data analysis followed three stages: reduction, presentation, and conclusion drawing. Findings indicate that while BAZNAS Ajatappareng has engaged in collaborative efforts with multiple stakeholders, certain aspects particularly human resource capacity and impact assessment remain suboptimal. The study recommends adopting best practices from other BAZNAS branches with proven success in zakat collection to strengthen future collaborative strategies.